Cave Explorers and Geoconservation in the North of England – a Changing Paradigm? - Philip Murphy; Sam Allshorn (Geoconservation Research)
Recent cave exploration in the Yorkshire Dales glaciokarst of the north of England has mainly been achieved through the removal of sediment infill from passages and entrances. This has resulted in the linking of previously fragmented cave systems to produce the world class Three Counties Cave System. This work has resulted in a growing appreciation by cave explorers of the need to conserve the delicate underground environment. A number of new techniques and approaches have been developed in order to limit the effects of exploratory digging on the cave system along with active efforts to clean up the underground legacy of previous generations of cave explorers. These techniques and approaches pioneered here may have wider applicability to karst areas elsewhere in the world where cave exploration has reached a phase which includes the digging through sediment blockages.